Stuff instead of a memoir - Lippard, Lucy R. 1937- (New Village Press, 2023)
Stuff: Instead of a Memoir is a short, abundantly illustrated autobiography of the American art writer, activist, and sometime curator Lucy R. Lippard. Describing tchotchkes, photographs, and art in her unpretentious New Mexico home, the author informally narrates key events and relationships in her 86-year-long, highly creative life, starting with her family roots and her childhood in New York, Louisiana, Virginia, and Maine. Through anecdotal and often humorous memories, we follow the author through her youth, adulthood, relationships, and her thirty-five years in New York City, where she organized dozens of exhibitions, authored hundreds of articles, and co-founded Heresies: A Feminist Journal of Art and Politics, the artist's-book center Printed Matter, and activist artists group PAD/D. Lippard touches on the roles she played in Conceptual Art and the Feminist Art movement in the 1960s through the 1980s. Her accounts of more recent years focus on the art, landscape, culture, and communities of the American Southwest, where she moved in the early 1990s. This "anti-memoir" also mentions Lippard's twenty-five books, but few of her many honors.
Keywords: Lippard, Lucy R. -- 1937-; Lippard, Lucy R. / Biography; Women art critics / United States / Biography; Art critics / United States / Biography; Women authors, American / United States / Biography; Authors, American / United States / Biography; Feminists / United States / Biography; Feminism and the arts; Lippard, Lucy R.; Autobiography / Women authors; Feminists; United States; Biographies; Autobiographies; Illustrated works; Autobiografie